1. ## differentiation

I need help with the following derivatives

y= (e^1/x) / x^2

f(t) = t ln(5t)

2. Could you show us what exactly is giving you trouble? What do you get when you attempt them?

3. Originally Posted by tim_mannire
I need help with the following derivatives

y= (e^1/x) / x^2

f(t) = t ln(5t)

USE QUOTIENT RULE ON THE FIRST ONE AND PRODUCT rULE ON THE SECOND ONE. SHOW YOUR WORK IF YOU GET STUCK!

4. Using the rules you suggested i got

dy/dx = ((x^2)(e^1/x) - (e^1/x)(2x)) / x^4

f ' (t) = (1/5t) (t)

are they correct?

5. Originally Posted by tim_mannire
Using the rules you suggested i got

dy/dx = ((x^2)(e^1/x) - (e^1/x)(2x)) / x^4

f ' (t) = (1/5t) (t)

are they correct?
For dy/dx it appears you've not differentiated $\displaystyle e^{1/x}$ correctly

It's easier if you sub $\displaystyle u = \frac{1}{x}$ and then use the chain rule.

--------------------------------------------------

For the second one remember the chain rule

$\displaystyle \frac{d}{dx} \ln [f(x)] = \frac{f'(x)}{f(x)}$

6. thanks for your help. I have tried what you suggested but I just don't understand . A complete working of the question using the rules would help me to understand.

thank you

7. Originally Posted by tim_mannire
thanks for your help. I have tried what you suggested but I just don't understand . A complete working of the question using the rules would help me to understand.

thank you
$\displaystyle y = \frac{e^{1/x}}{x^2}$

For this we need to use the quotient rule which is: $\displaystyle y' = \frac{vu' - uv'}{v^2}$

In your case $\displaystyle u = e^{1/x}$ and $\displaystyle v = x^2$

I will differentiate the numerator as that's what seems to be the issue then you can try using my value of $\displaystyle u'$ in the quotient rule. FYI my final answer is $\displaystyle \frac{dy}{dx} = \frac{e^{1/x}(2x-1)}{x^4} = -\frac{e^{1/x}(1-2x)}{x^4}$

To find u' (du/dx) we need to work out $\displaystyle \frac{d}{dx} e^{1/x}$.
For simplicity and clarity's sake let $\displaystyle t = \frac{1}{x}$. From the chain rule we know that $\displaystyle \frac{du}{dx} = \frac{du}{dt} \cdot \frac{dt}{dx}$

Due to this substitution we can rewrite u as $\displaystyle u = e^t$.

Differentiating this function is easy: $\displaystyle \frac{du}{dt} = e^t$

Similarly 1/x is also easy to differentiate: $\displaystyle \frac{dt}{dx} = -\frac{1}{x^2}$

From the chain rule above: $\displaystyle u' = \frac{du}{dx} = \frac{du}{dt} \cdot \frac{dt}{dx} = e^t \cdot \frac{1}{x^2}$

Since $\displaystyle t = \frac{1}{x}$ we get $\displaystyle u'$ in terms of x:

Therefore $\displaystyle u' = -\frac{1}{x^2}\,e^{1/x}$

8. Originally Posted by tim_mannire
f(t) = t ln(5t)
For this one, it is

$\displaystyle f'(t) = t \cdot [\ln(5t)]' + [t]' \cdot \ln(5t)$

$\displaystyle = t \cdot \frac{5}{5t} + 1 \cdot \ln(5t)$